2022
DOI: 10.1371/journal.pgen.1010059
|View full text |Cite
|
Sign up to set email alerts
|

Comparative therapeutic strategies for preventing aortic rupture in a mouse model of vascular Ehlers-Danlos syndrome

Abstract: Vascular Ehlers-Danlos syndrome is a rare inherited disorder caused by genetic variants in type III collagen. Its prognosis is especially hampered by unpredictable arterial ruptures and there is no therapeutic consensus. We created a knock-in Col3a1+/G182R mouse model and performed a complete genetic, molecular and biochemical characterization. Several therapeutic strategies were also tested. Col3a1+/G182R mice showed a spontaneous mortality caused by thoracic aortic rupture that recapitulates the vascular Ehl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Our UPR data provide direct evidence that ER stress and UPR activation are a feature of vEDS. This is supported by signs of ER stress in the vasculature of a vEDS mouse model 21 , defects in ER homeostasis on transcriptomic analysis of fibroblasts 33,34 , and a delay in protein folding due to COL3A1 glycine mutations in a bacterial expression system 35 . The detection of ER stress in fibroblasts but limited evidence from smooth muscle cells 20,21 could reflect a cell type-dependent mechanism whereby UPR activation may occur more readily due to the higher expression of ECM proteins in fibroblasts compared to smooth muscle cells (Human Protein Atlas) 36 ; Dataref: Karlsson et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Our UPR data provide direct evidence that ER stress and UPR activation are a feature of vEDS. This is supported by signs of ER stress in the vasculature of a vEDS mouse model 21 , defects in ER homeostasis on transcriptomic analysis of fibroblasts 33,34 , and a delay in protein folding due to COL3A1 glycine mutations in a bacterial expression system 35 . The detection of ER stress in fibroblasts but limited evidence from smooth muscle cells 20,21 could reflect a cell type-dependent mechanism whereby UPR activation may occur more readily due to the higher expression of ECM proteins in fibroblasts compared to smooth muscle cells (Human Protein Atlas) 36 ; Dataref: Karlsson et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…Recent data from mouse models explored the efficacy of modulating more downstream ERK signalling mechanisms 20 . We set out a complementary approach focusing on more upstream mechanisms that may be applicable to multiple mutations and tissues to help overcome recently observed allele specific outcomes of treatments targeting these further downstream mechanisms [20][21][22] . Excitingly PBA rescued both the ER stress and improved the quality of the secreted collagen without increasing levels of secretion per se, as determined by the susceptibility to trypsin digest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collagens are a major constituent of the pial membrane which plays a critical role in lamination and neuronal migration within the fetal brain. Legrand et al (2022) showed that ‘knock-in’ mice had a significant therapeutic response to Losartan, reversed on stopping and worsened by exogenous angiotensin II. Other antihypertensive agents were ineffective.…”
Section: Mouse Modelsmentioning
confidence: 99%